Study of adsorption cooling and desalination system - Wang, Marvin Jiansong. (2013)
This project aims to present the conceptual model of adsorption desalination (AD) system and explains various roles of the mechanism in the AD system. Simulation was done to evaluate the optimal operating conditions that uses mass and energy balance. The AD system is capable of generating portable water and also has cooling capacity. Focusing on performance of the AD system, keys inputs such as hot-water (Thot) temperature, evaporator (Tevap) temperature and cycle time (tcycle) was modified. Simulation parameters are stated and focus on a two reactor bed AD system. Graphs was plotted out based on Specific Water Production (SWP), Cooling Capacity and Coefficient of Performance (COP) versus hot-water (Thot) temperature, evaporator (Tevap) temperature and cycle time (tcycle). Results show that cooling performance will be throttled if water production is prioritised and vice versa. Recommended operating parameter for water production, cooling performance or both was given at the end of the report.